Chemical Identity of Hypothalamic Neurons Engaged by Leptin in Reproductive Control - Ratra, Dhirender V. (J Chem Neuroanat, 2014)
The adipocyte-derived hormone leptin plays a critical role as a metabolic cue for the reproductive system. Conditions of low leptin levels observed in negative energy balance and loss-of-function mutations of leptin or leptin receptor genes are characterized by decreased fertility. In recent years, advances have been made identifying possible hypothalamic neurons relaying leptin’s neuroendocrine control of reproductive function. Studies from different laboratories have demonstrated that leptin action in the hypothalamo-pituitary-gonadal (HPG) axis is exerted via hypothalamic interneurons regulating gonadotropin-releasing hormone (GnRH) cells, oppose to direct action on GnRH neurons. Following this observation, studies focused on identifying leptin responsive interneurons. Using a Cre-loxP system to re-express or delete the leptin receptor long form (LepRb) from Kisspeptin neurons, our laboratory found that leptin’s action on Kiss1 cells is neither required nor sufficient for leptin’s role in reproductive function. Endogenous re-expression of LepRb however, in glutamatergic neurons of the ventral premammilary nucleus (PMV) or ablation of agouti-related protein (AgRP) neurons from leptin signaling-deficient mice are both sufficient to induce puberty and improve fertility. Recent studies have also shown that leptin action in first order GABAergic neurons is required for fertility. Together, these studies begin to delineate key neuronal populations involved in leptin’s action in reproduction. In this review, we discuss recent advances made in the field and highlight the questions yet to be answered.